Harmonizing national law with inter-American human rights law: Evidence from Mexico. Issue 4 (1st October 2016) - Aguiar-Aguilar, Azul A.
ABSTRACT: Conventionality review is a recent Latin American doctrine seeking that states which had ratified the American Convention of Human Rights verify the conformity of their national laws to norms of the Convention. In Mexico, several changes have placed the country in a better position to follow this inter-American doctrine: 1) a 2011 human rights constitutional amendment; and 2) an interpretation handed down by the Mexican Supreme Court after its appraisal of the Rosendo Radilla-Pacheco case. These events allow all judges in the country (federal and local) to disregard national laws if they contravene norms established in the Convention or the Constitution. How then are these changes operating in practice? This article explores the extent to which conventionality review is being used by intermediate level court's judges and defenders in the states of Jalisco, Nuevo Leon, and Oaxaca.